STUDI PELIBATAN MASYARAKAT LOKAL DALAM PENGEMASAN PRODUK DESA WISATA CATUR KINTAMANI BALI - I Gede Gian Saputra (JURNAL KEPARIWISATAAN, 2020)
The study aims to identify community attitudes in the development of tourism villages and to analyze the forms of community involvement in packaging the Catur Tourism Village products. Theories and concepts used were the tourism area life cycle, index theory (irritation index), concept of community-based tourism (CBT), concept of tourism products, and concept of tourism village 4.0. The research used a qualitative research approach using descriptive qualitative data analysis techniques. The results showed most forms of community involvement in packaging Catur Tourism Village products exist at the implementation stage, then planning and decision-making. Even though most of the people involved in packaging Catur Tourism Village products, the number of people who was not involved was still quite high. This is where the role of the tourism village manager is needed to be able to bridge the aspirations of people who want to be involved in the development of the Catur Tourism Village. Catur Village local government should be able to formulate community engagement strategies so that the community can be optimally involved in packaging Catur Tourism Village products.